The Emerging Role of Targeted Therapy and Immunotherapy in the Management of Brain Metastases in Non-Small Cell Lung Cancer - Wong, Annick (Frontiers in Oncology, 2017)
Lung cancer is the worldwide leading cause of cancer-related mortality in men and second leading in women. Brain metastases (BM) account for 10% of non-small cell lung cancer (NSCLC) patients at initial presentation, with another 25-40% developing BM during the course of their disease. In the last decade, the field of precision oncology has led to the discovery of a multitude of heterogenous molecular abnormalities within NSCLC as well as the development of tyrosine kinase inhibitors (TKIs) that target them. In this review, the focus will be on targeted therapies and immunotherapy that show efficacy in BM rather than conventional treatment for multiple brain metastases (such as surgical resection, WBRT or stereotactic radiosurgery).